Navigate your stars - Ward, Jesmyn (Scribner, 2020)
"For Tulane University's 2018 commencement, Jesmyn Ward delivered a stirring speech about the value of hard work and the importance of respect for oneself and others. Speaking about the challenges she and her family overcame, Ward inspired everyone in the audience with her meditation on tenacity in the face of hardship. Ward's moving words will inspire listeners as they prepare for the next chapter in their lives, whether, like Ward, they are the first in their families to graduate from college or are preceded by generations, or whether they are embarking on a different kind of journey later in life."--Amazon.com.